Determinasi Profitabilitas Pada Perusahaan Manufaktur Sektor Barang Konsumsi: Determination of Profitability in the Consumer Goods Manufacturing Company - Evi Husnah; Iwan Setiadi (Journal of Accounting Science, 2020)
This study aims to analyze the effect of Current Ratio, Total Asset Turnover, Debt to Equity and Firm Size on Profitability in Manufacturing Companies in the Consumer Goods Industry Sector in 2011-2017. The design of this study is causal associative. The population of this study includes all Manufacturing Companies of the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange during 2011-2017. Sample selection techniques using purposive sampling method and research data obtained by 20 companies. The data analysis technique is done by using Descriptive Statistical Analysis, Classic assumption test which includes normality test, autocorrelation test, heteroscedasticity test and multicollinearity test, Multiple Linear Regression Test and Model Feasibility Test which include Determination Coefficient Test, T test and F Test. The research results partially show the Current Ratio has a negative and not significant effect on Return on Assets. Total Asset Turnover and company size have a positive and significant effect on Return on Assets, and Debt to Equity Ratio has a negative and significant effect on Return on Assets. But Simultaneously it is known that CR, TATO, DER and Size have a significant effect on ROA.